Development and validation of an equine nerve block simulator to supplement practical skills training in undergraduate veterinary students. (27th April 2013) - Gunning, P.; Smith, A.; Fox, V.; Bolt, D. M.; Lowe, J.; Sinclair, C.; Witte, T. H.; Weller, R.
Abstract : Lameness is the most common presenting complaint in equine practice. Performing diagnostic nerve blocks is an integral part of any lameness work‐up, and is therefore an essential skill for equine practitioners. However, the opportunities for veterinary students to practice this skill are limited. The aim of this study was to design and validate an equine nerve block simulator. It was hypothesised that the simulator would improve students' ability and enhance their confidence in performing nerve blocks. A simulator was built using an equine forelimb skeleton and building foam. Wire wool targets were placed under the foam in the positions corresponding to the anatomical location of the most palmar digital, abaxial and low four‐point nerve blocks and attached to an electrical circuit. The circuit became complete when the operator placed a needle in the correct position and immediate audible feedback with a buzzer was provided. To validate the simulator, it was compared with two established teaching methods: cadaver training and theoretical training with a hand‐out. Cadaver‐trained students achieved the best results (73 per cent correct blocks), compared with simulator‐trained students (71 per cent correct blocks), and a hand‐out trained group (58 per cent correct blocks). Feedback obtained with a questionnaire showed that students enjoyed simulator training more, and that they felt more confident in performing diagnostic nerve blocks than the other two groups. The equine nerve block simulator provides a safe, cost‐effective method to supplement the teaching of diagnostic analgesia to undergraduate veterinary students.